2007
DOI: 10.1002/cne.21482
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the melanin‐concentrating hormone neurons activated during paradoxical sleep hypersomnia in rats

Abstract: Although the main nodes of the neuronal network that regulate paradoxical sleep (PS), also called rapid eye movement sleep, have been identified in rodents, it still needs to be more thoroughly described. We have recently shown that 58% of a hypothalamic neuronal population, the melanin-concentrating hormone (MCH) neurons, are activated after a PS hypersomnia and that MCH, when injected intracerebroventricularly, induces a dose-dependent increase in PS. This suggests that MCH plays a role in PS regulation. Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
46
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 37 publications
8
46
1
Order By: Relevance
“…CART was detected in the hippocampus (Abraham et al, 2005), and promoted the survival and differentiation of neurons in primary hippocampal cell culture (Wu et al, 2006). Hanriot et al (2007) suggested that melaninconcentrating hormone (MCH) cells in the hypothalamus, some of which co-contained CART, may be involved in the memory processing. Previously, it was reported that swimming in MWM generated stress, which subsides gradually during the training sessions (Aguilar-Valles et al, 2005).…”
Section: Effect Of Cart In the Modulation Of Acquisition And Retrievamentioning
confidence: 98%
“…CART was detected in the hippocampus (Abraham et al, 2005), and promoted the survival and differentiation of neurons in primary hippocampal cell culture (Wu et al, 2006). Hanriot et al (2007) suggested that melaninconcentrating hormone (MCH) cells in the hypothalamus, some of which co-contained CART, may be involved in the memory processing. Previously, it was reported that swimming in MWM generated stress, which subsides gradually during the training sessions (Aguilar-Valles et al, 2005).…”
Section: Effect Of Cart In the Modulation Of Acquisition And Retrievamentioning
confidence: 98%
“…One third of these GABAergic neurons werealso immunoreactive for the neuropeptide Melanin Concentrating Hormone (MCH). Almost 60% of all the MCH-immunoreactive neurons counted in PeF, ZI and LHA were c-Fos+ [39,46]. We recently further demonstrated that these neurons co-contain nesfatin, another recently discovered peptide [47].…”
Section: Role Of the Posterior Hypothalamus In Particular Mch Neuronmentioning
confidence: 99%
“…Later, a strong connection between MCH and REMS has been revealed (Kitka et al 2011;Torterolo et al 2011). Local or intracerebroventricular administration of MCH to rodents caused a marked increase in REMS; moreover, an elevated activation (increased Fos immunoreactivity) of MCH-expressing neurons has been reported during REMS rebound after a long-term sleep deprivation (Hanriot et al 2007;Kitka et al 2011;Modirrousta et al 2005;Peyron et al 2009;Torterolo et al 2011;Verret et al 2003). The increase in the time spent in REMS and the decrease in the REMS latency during the rebound following sleep deprivation are both changes similar to those described in depression.…”
Section: Introductionmentioning
confidence: 99%